Advanced perspective on the synchronized bifunctional activities of P2-type materials to implement an interconnected voltage profile for seawater batteries. Issue 23 (30th May 2018) - Manikandan, Palanisamy; Kishor, Koshal; Han, Jinhyup; Kim, Youngsik
Abstract : Na0.5 Co0.5 Mn0.5 O2 comprising an integrated voltage profile for a seawater battery and showing intercalation–deintercalation and OER/ORR characteristics in comparison with a carbon felt and 20% Pt/C catalyst at 0.1 mA for 5 h. Abstract : Electrical energy storage on a large-scale is essential to the ultimate use of natural and clean renewable energy sources. Recently, research and development attempts toward a room-temperature seawater battery (SWB) have been rejuvenated, as SWBs are considered capable, low-cost substitutes to the existing Li-ion battery technology for large-scale usage. In this work, P2-type layered Na0.5 Co0.5 Mn0.5 O2 oxide was discovered for the first time to be a new option of a bifunctional cathode electrocatalyst material for an aqueous SWB, with two kinds of voltage profiles, a slope and flat voltage region, corresponding to the Na + ion intercalation–deintercalation reaction and OER/ORR catalytic activities in comparison with a carbon felt substrate and 20% Pt/C catalyst. A developed electrocatalyst for the cathode of the SWB demonstrated excellent activity and provided a discharge capacity of ∼30 mA h g −1 ascribed to Na + -ion intercalation–deintercalation reaction, while cyclic voltammetric analysis corroborated with the redox peak at 3.31/3.04 V for Co 3+/4+ redox species in comparison with a carbon felt substrate. Further, the OER and ORR catalytic activities of the electrocatalyst were confirmed with a full-cell seawater battery, which exhibited a lower voltage difference of 0.36 V and delivered a hard carbon discharge capacity of 183 mA h g −1 at 0.1 mA. Consequently, this cathode was demonstrated to have an integrated voltage profile for a seawater battery, showing its potential to work on a commercial scale.